English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-07 04:47:35 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

-(x*Cos[x]) + Sin[x]

2007-01-07 04:54:45 · answer #1 · answered by Raoof 2 · 0 0

you ought to break (xsinx dx) into u and dv. enable (x dx) be u and enable (sinx) be dv. Now considering that u=x dx, then du=dx, and because dv=sinx, then v=-cosx Now use your formula udv=uv-Int(vdu) that's Int(xsinx dx) = x(-cosx)-Int(-cosx dx), take the unfavourable out to circulate away -xcosx+Int(cosx dx) which equals: -xcosx+sinx+C that's your answer, do no longer overlook the consistent C

2016-12-12 06:10:24 · answer #2 · answered by cheng 4 · 0 0

Yay, integration by parts! I haven't done this in ... 16 years.

u = x
du = dx

dv = sinx dx
v = -cosx dx

∫ u dv = uv - ∫ v du

∫ x sinx dx = -x cosx - ∫ -cosx dx
= -x cosx + sinx + C

Not bad for an old pharte, eh?

2007-01-07 04:52:15 · answer #3 · answered by Jim Burnell 6 · 1 0

fedest.com, questions and answers